Nordiske sundhedsfremmende perspektiver på ældre menneskers deltagelse og tryghed - Mahler, Marianne; Clancy, Anne; Johannessen, Aud; Lind, Johanne; Liveng, Anne; Sarvimäki, Anneli; Stenbock-Hult, Bettina; Simonsen, Nina (Nordisk Tidsskrift for Helseforskning, 2020)
Nordic Health Promotion Perspectives on Older Adults Participation and Sense og Security Demographic changes and the growing elderly population in Scandinavia provide an incentive to study Health Ageing in the Nordic Countries. The chosen Nordic perspective takes into account commonalities and differences in socio-economic status, welfare systems, gender, history and culture. It also involves focusing on the health of individuals and populations. The Nordic perspective and the authors’ understanding of health and health promotion provide a backdrop for the essay. The authors are part of the Nordic Health Promotion Network (NHPRN), which is grounded in an ethics of health and well-being. This understanding highlights key values such as participation, justice and equality (freedom from discrimination), autonomy (independence). The authors focus mainly on the importance of participation and on the older person’s sense of security in this paper. We seek answers to what prevents and in which way Healthy Ageing can be promoted in the Northern countries. Concepts such as discrimination, retirement, dementia, nursing home residents’ access to nature and the elements, and the importance of relationships are illuminated.